Monthly water balance model for lateritic hill slope- a case study - Beena Thomas (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1996)
The groundwater balance of K. C. A. E .T. Campus, Tavanur, Kerala has been studied and a deterministic model has been developed for the prediction of depth to water table in this hill slope based on Darcy’s equation. The input data required are the precipitation, evapotranspiration, specific yield, initial water table, elevation of the points under consideration and the distance between the points. The weekly precipitation and evapotranspiration were calculated and from this the recharge to groundwater was estimated. The groundwater recharge was taking place only during the southwest monsoon season. The change in storage divided by the hydraulic gradient for a period without rainfall i.e., from 01 December 1994 to 16 February 1995 were determined. Using these values and other inputs in the model, the depth to water table for a period from 26 May 1994 to 25 May 1995 were estimated from the model. These values were compared with the observed values for the same period. It was found that the estimated values give a reasonable estimate of the depth to water table in the study area. This model can be used to predict the changes expecting in the water level in a particular region. The model has several areas of application in the fields of groundwater resource development and irrigation. The infiltration characteristics of the selected area was evaluated and observed that the infiltration rate was increasing towards the higher elevation. The model was simulated for different percentages of effective rainfall and found that, at 50 per cent it accounts as groundwater recharge and the rest as surface runoff.